LYNGA 1, a small open cluster containing a red-supergiant member - Vazquez, Ruben Angel (2003)
We presen t CCD UB VR I (Cousins system) photometric observations complemented with spectroscopic and polarimetric observations that were carried out in the open cluster Lyng ˚a 1. Our data indicate that the cluster reddening is E B−V = 0 .45 ± 0 .03, the ratio A V /E B−V = R suggests that the extinction law may b e slightly anomalous ( R ≈ 3 .5) and that the cluster distance modulus is V0 − MV = 11 .40 ± 0 .2. The age of Lyng ˚a 1 is bet ween 100 and 125 Myr according to a fitting of theoretical iso chrones, and the slop e of its mass spectrum is x ≈ 1 .7. The brightest red star in the field is a cluster mem ber of spectral typ e K2 II–Ib.